If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) * 5 = 9 Reorder the terms: 2(3 + x) * 5 = 9 Reorder the terms for easier multiplication: 2 * 5(3 + x) = 9 Multiply 2 * 5 10(3 + x) = 9 (3 * 10 + x * 10) = 9 (30 + 10x) = 9 Solving 30 + 10x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 10x = 9 + -30 Combine like terms: 30 + -30 = 0 0 + 10x = 9 + -30 10x = 9 + -30 Combine like terms: 9 + -30 = -21 10x = -21 Divide each side by '10'. x = -2.1 Simplifying x = -2.1
| 11p=144 | | (-2x+2)=y | | 7k-45=4 | | 1-3x=8-4x | | 5z=48 | | .35(5+y)=12 | | 17-n=341 | | 25n+30=50 | | sen(6x)=0 | | 12=9a-15 | | (12*8)=(k*7) | | 27x-64+210-x= | | 3q-5=1 | | 2x+16=8x-20 | | a+6a-3a= | | 6n+8=36 | | 2l+-2=15 | | 7x-122+2x=103 | | 7x+42=x+60 | | -x+15=x+7 | | 0.26=log*x | | d=15(30) | | 3x-13/4=2x | | 4(5x-5)=-3 | | (x-3.2)(x-3/2)=0 | | x+(x-7)+3(x-7)=63 | | 6n+19=63 | | 2443=x*.0625 | | 6x-15=x+10 | | 8p=63 | | x+(x+7)+3(x+7)=63 | | 2(t-1)=32+2t |